Spontaneous Heterotopic Triplet Pregnancy With Tubal Rupture - Lima Arsala MBBS, BBMedSci; Dennis Danso MBBS, RANZCOG MRCOG (SAGE Publishing, 2014)
The recent increase in heterotopic pregnancies has been largely attributed to the increased use of assisted reproduction technologies. We report the rare case of a multiparous woman with a spontaneous conception resulting in a triplet heterotopic pregnancy: a twin intrauterine pregnancy and a single right tubal ectopic pregnancy. Heterotopic pregnancy is a rare and potentially life-threatening condition in which simultaneous gestations occur at 2 or more implantation sites. It is infrequent in natural conception cycles, occurring in 1:30 000 pregnancies. However, the prevalence is rising with the increased use of assisted reproduction techniques to that of 1:100 to 1:500 in these patient subgroups, highlighting the need to incorporate it into a clinician's diagnostic algorithm.